CTCF and cellular heterogeneity - Gang Ren; Keji Zhao (Cell & Bioscience, 2019)
Abstract Cellular heterogeneity, which was initially defined for tumor cells, is a fundamental property of all cellular systems, ranging from genetic diversity to cell-to-cell variation driven by stochastic molecular interactions involved all cellular processes. Different cells display substantial variation in gene expression and in response to environmental signaling even in an apparently homogeneous population of cells. Recent studies started to reveal the underlying mechanisms for cellular heterogeneity, particularly related to the states of chromatin. Accumulating evidence suggests that CTCF, an important factor regulating chromatin organization, plays a key role in the control of gene expression variation by stabilizing enhancer–promoter interaction.